Kontribusi Daya Ledak Otot Tungkai dan Daya Tahan Otot Perut terhadap Kemampuan Lari Sprint 100 Meter pada Siswa Madrasah Aliyah Negeri 2 Banda Aceh - Safrizal, Safrizal (Jurnal Ilmiah Guru Madrasah, 2022)
The purpose of this study is to determine the contribution of explosive leg muscle power and abdominal muscle endurance to the ability to sprint 100 meters in students participating in extracurricular activities at Madrasah Aliyah Negeri 2 Banda Aceh. Leg muscle explosive power, measured by the standing broad jump test; abdominal muscle endurance, measured by the bent-knee sit-up test; and 100-meter sprint ability, measured by the 100-meter sprint test. Data is processed using statistical techniques in the form of calculating the mean value, standard deviation, and correlation test. The results of this study indicate that there is a positive and significant relationship between limb muscle explosive power and the ability to sprint 100 meters (r = 0.87). There is a positive and significant relationship between abdominal muscle endurance and the ability to sprint 100 meters (r = 0.81). The ability to sprint 100 meters is positively and significantly related to explosive leg muscle power and abdominal muscle endurance (R_(Y.X_1 X_2) = 0.89). The hypothesis testing results show that Fcount = 41.68 and Ftable = 3.44. So the explosive power of the leg muscles and abdominal muscle endurance have a significant contribution to the ability to run the 100-meter sprint. Abstrak Artikel ini bertujuan untuk mengetahui kontribusi Daya Ledak Otot Tungkai dan Daya Tahan Otot Perut Terhadap Kemampuan Lari Sprint 100 meter pada Siswa Madrasah Aliyah Negeri 2 Banda Aceh pada kegiatan Ekstrakurikuler. Daya ledak otot tungkai, diukur dengan standing broad jump test, daya tahan otot perut, diukur dengan menggunakan tes bent knee sit up, dan kemampuan lari sprint 100 meter diukur dengan tes lari sprint 100 meter. Data diolah dengan menggunakan teknik statistik dalam bentuk perhitungan nilai rata-rata, standar deviasi dan uji korelasional. Hasil penelitian ini menunjukkan bahwa terdapat hubungan yang positif dan signifikan antara Daya Ledak Otot Tungkai dengan Kemampuan Lari Sprint 100 meter sebesar (r = 0,87). Terdapat hubungan yang positif dan signifikan antara Daya Tahan Otot Perut terhadap Kemampuan Lari Sprint 100 meter sebesar (r = 0,81). Terdapat hubungan yang positif dan signifikan antara Daya Ledak Otot Tungkai dan Daya Tahan Otot Perut terhadap Kemampuan Lari Sprint 100 meter sebesar ( = 0,89). Hasil pengujian hipotesis menunjukkan bahwa Fhitung = 41,68 ≥ Ftabel = 3,44. Maka Daya Ledak Otot Tungkai dan daya tahan otot perut mempunyai kontribusi yang signifikan terhadap kemampuan lari Sprint 100 meter.